Composition of Trees Grown Surrounding Water Springs at Two Areas in Purwosari Pasuruan, East Java - soejono soejono (Journal of Tropical Life Science, 2012)
The aim of the research was to find out the composition of trees grown surrounding water springs at two areas in Purwosari, Pasuruan, East Java. Eleven plots for each area were observed. The data were analyzed using Mueller-Domboiss method to calculate their importance value indexes, while Shannon-Wieners formula was used for determining the diversity index. The coordinate and altitude of every water spring or its groups site was determined using Geographical Position System (GPS) to know their positions on the map. The result indicated that there were at least 30 families, 49 genera which consisted of 68 species of trees grown surrounding water springs at the first area with 5.49 of diversity index, while the second area, consisted of 34 families, 63 genera and 79 species of trees with 5.24 diversity index. The diversity of trees species from Moraceae was the highest among other families, both at the first and the second area, whereas, trees species having a significant important value index included Bambusa blumeana, Dendrocalamus asper, Ficus racemosa, Horsfieldia irya and Ficus virens. The position of the springs in the two areas within the sub-districts of Purwosari is in the range of 7º44'448